Human cadaver burial depth affects soil microbial and nutrient status - Pawlett, Mark; Rickson, R. Jane; Niziolomski, Joanna; Churchill, Sophie; Kešner, Michal (Equinox Publishing, 2019)
this can enhance the natural recycling of nutrients to the soil through improved interactions between the corpse and the soil ecosystem. However, there is a paucity of knowledge describing the interactions between the human cadaver and soil microbiology at any depth. The effects of shallow were compared to standard burial depth on soil chemical (available nitrogen and phosphorus, and organic matter) and microbial (total biomass and activity, fungal biomass, and microbial community composition) characteristics in two soil types (sandy loam and clay). Measurements were taken six and eight weeks after the burial of fresh pork ribs (used as a substitute for the human cadaver). Quantities of plant available nitrogen, as both ammonium-N (clay soil) and nitrate-N (both soil types), were greater where the pork was shallow buried. In addition, there was a shift in the composition of the bacterial component of the soil microbial community where the pork was shallow buried compared to deep burial (sandy loam soil only). There were no differences between the two burial depths (both soil types) in soil organic matter, available phosphorus, total microbial biomass or activity, or the proportion of fungi within the microbial community. The differences in available nitrogen and the lack of differences in the bacterial community composition between the two depths for the clay soils is likely to be due to reduced pore space and hence reduced oxygen at depth, which would dominate any response of the microbial community to the decomposing meat.
Keywords: cadaver decomposition; microbiology; soil depth